The Potensi Ikan Gabus (Ophiocephalus stratius) untuk Meningkatkan Kadar Albumin Pada Penderita Hipoalbuminemia - Agnes Trilansia Pratiwi (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2021)
ABSTRACT Introduction: Hypoalbuminemia is an abnormal condition indicated by low levels of albumin in the blood. Hypoalbuminemia can be caused by decreased albumin production or increased albumin loss through the kidney, gastrointestinal tract, skin, or extravascular space or increased albumin catabolism or a combination of 2 or more of these mechanisms. Hypoalbuminemia is associated with poor functional status, longer duration of hospitalization and higher morbidity and mortality. In Indonesia, 40-50% of patients with hypoalbuminemia due to malnutrition experience of hypoalbuminemia, whereas 12% has severe hypoalbuminemia. Oral administration of high protein nutrition and parenteral albumin are alternative treatments for hypoalbuminemia. Method: The article was compiled using the literature review method, involving 24 literatures sources from books and national or international journals. Discussion: Snakehead fish (Ophiocephalus stratius) has a high protein content, especially albumin. The high albumin content of snakehead fish extract can function as a source of amino acids needed for albumin synthesis. Various effects of snakehead fish extract have been reported including accelerating wound healing, antinociceptive, anti-inflammatory activity, and having an important effect in hypoalbuminemia by increasing albumin levels in the blood. Snakehead fish extract can also increase IGF-1 levels which may reduce inflammation which may explain the correlation with increased albumin levels. Conclusion: The amino acid content in snakehead fish (Ophiocephalus striatus) has an effect on increasing albumin levels in hypoalbuminemia patient.